Mathematical problems: the advantages of visual strategies - Vale, Isabel (2018)
The rapid evolution of today’s world requires that all students have access to an education that values creativity, critical thinking and problem solving. It means motivating students to use multiple strategies when solving a problem, including the visual ones as an important support in solving all kinds of problems, including those in which the visual component is not evident. So, teachers should include practices that lead students to think visually and develop this ability through experiences that require such way of thinking. In this context, we discuss the advantages of using visual strategies when solving problems with multiple approaches, illustrating those ideas with some examples.